The shape of Korea's future : South Korean attitudes toward unification and long-term security issues - Levin, Norman D.; Han, Yong-Sup.; Rand eBooks (Santa Monica, CA : RAND, 1999)
South Koreans are moving beyond both the historical and Cold War legacies in their thinking about Korea's long-time security. This major conclusion, which emerges from this report analyzing South Korean attitudes toward unification and long-term security issues, is bolstered by additional findings suggesting potentially significant movement in almost all areas of South Korea's traditional security perspectives. This includes significantly reduced South Korean security anxieties and increased confidence in Korea's place in the regional and global orders. It also includes greater hesitance about reunification, markedly altered attitudes toward Japan, increased discernment about the role of the U.S.-Republic of Korea (ROK) alliance, and heightened uncertainty about the long-term value of the U.S. regional military presence. Such attitudes could have important implications for both U.S. policy and U.S.-ROK security relations.
"Center for Asia-Pacific Policy."
Includes bibliographical references.
Also available on the internet via WWW in PDF format.
Keywords: Korean reunification question (1945- ) -- Public opinion; Koreans -- Korea (South) -- Attitudes; National security -- Korea (South) -- Public opinion; Korea (South) -- Foreign relations -- Public opinion; Korea (South) -- Politics and government -- 1988- -- Public opinion; Electronic books